1997
DOI: 10.1159/000239529
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Susceptibility of Clinical Group A, B, C, F, and G β-Hemolytic Streptococcal Isolates to 24 Antimicrobial Drugs

Abstract: A total of 312 clinical β-hemolytic streptococcal isolates (Streptococcus pyogenes, group A = 63; Streptococcus agalactiae, group B = 145; group C = 50; group F = 27; group G = 27) were examined for susceptibility to 23 and 24 antimicrobial drugs with the Bauer-Kirby agar disk diffusion and the agar dilution method, respectively. Sheep blood Mueller-Hinton agar served as the reference medium. Wilkins-Chalgren agar supported optimal growth of group A and B, but not of all group C, F, and G streptococci. The gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
35
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 40 publications
13
35
0
3
Order By: Relevance
“…The high resistance (25.5 %) of GAS to tetracycline reported here is comparable to the global rise noticed (Aggarwal et al, 1984;Dhakal et al, 2010;Jain et al, 2008;Lloyd et al, 2007;Ray et al, 2010;Smeesters et al, 2010;Traub & Leonhard, 1997;Zaoutis et al, 1999) that has been assigned to polyclonal dissemination of resistance types, as antibiotic resistance encoded by transposable elements does occur in GAS. GAS resistance (3.9 %) to chloramphenicol and susceptibility to vancomycin reported in this study are similar to results from previous reports (Jain et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The high resistance (25.5 %) of GAS to tetracycline reported here is comparable to the global rise noticed (Aggarwal et al, 1984;Dhakal et al, 2010;Jain et al, 2008;Lloyd et al, 2007;Ray et al, 2010;Smeesters et al, 2010;Traub & Leonhard, 1997;Zaoutis et al, 1999) that has been assigned to polyclonal dissemination of resistance types, as antibiotic resistance encoded by transposable elements does occur in GAS. GAS resistance (3.9 %) to chloramphenicol and susceptibility to vancomycin reported in this study are similar to results from previous reports (Jain et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
“…Worldwide data suggest an increased resistance of GAS to macrolides, ranging from 0. A Cd E At Cw T C Nv Ak G Throat isolates 11 + 2 2 2 2 2 + 2 2 2 57 2 2 2 + + + 2 2 2 2 85 2 + + 2 2 2 2 2 2 2 Skin isolates 12 2 2 2 2 + 2 + + 2 2 22.8 2 2 2 + 2 2 + 2 2 2 44 2 2 2 + 2 2 2 + 2 2 44 + 2 2 + 2 + 2 2 2 2 44 2 2 + 2 2 2 2 + 2 2 44 2 2 2 + 2 2 2 + 2 2 44 2 2 2 + + + 2 + 2 2 44 2 2 2 2 2 2 2 2 2 2 49 2 2 2 + + + 2 2 2 2 75.1 2 2 2 2 2 + 2 + 2 2 81 2 2 + 2 2 2 2 2 + 2 81 2 2 2 2 2 + 2 + 2 + 85 2 2 2 2 2 + 2 + 2 2 RF isolates 11 2 2 2 2 2 + 2 + 2 2 67 2 2 2 2 2 + 2 + 2 2 Invasive disease isolates 58 2 2 2 2 2 + + 2 2 2 87 2 2 + 2 2 + 2 2 + 2 95 2 2 2 2 2 + 2 + + 2 Rowe et al, 2009;Traub & Leonhard, 1997); a review of Indian literature showed a gradual increase upto 29.4 % up until 2010 (Brahmadathan et al, 2005;Capoor et al, 2006;Dhakal et al, 2010;Lloyd et al, 2007;Mathur et al, 2002). The absence of, or very low, erythromycin resistance among GAS from pharyngitis and RF patients in the present study is quite similar to previous findings (Brahmadathan et al, 2005;Rijal et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…By agar-dilution assay for MIC determination (National Committee for Clinical Laboratory Standards, 2000b), we observed that the results were similar to those of the disc-diffusion assay, except for one isolate that showed intermediate susceptibility to erythromycin by the discdiffusion test and resistance by MIC determination. Similar discrepancy has been reported before (Traub & Leonhard, 1997). Total erythromycin resistance in the period of study was 5·4 %, which is similar to values reported recently in other countries (Fernandez et al, 1998;de Azavedo et al, 2001).…”
supporting
confidence: 91%
“…Macrolides are a useful alternative therapy in penicillinallergic patients; however, emergence of strains resistant to macrolides has been observed in several countries, at a frequency ranging from 2 to 46 % (Traub & Leonhard, 1997;Hsueh et al, 2001). …”
mentioning
confidence: 99%
“…A high rate of tetracycline resistance was noted in our study, as was described in other studies performed in different countries: USA (96 %), Germany (74.5 %) and France (88.1 %) (Lin et al, 2000;Traub & Leonhard, 1997;De Mouy et al, 2001).…”
supporting
confidence: 89%